Modelowanie zależności zastosowanie w zarządzaniu ryzykiem - Heilpern, Stanisław (Modelling of Dependence - Application in the Risk Management, 2007)
Three methods of modelling of dependence of random variables and examples of the application of these methods to risk management are presented. We study the application process in the context of ruin and the credit solvency. In the first method, the dependent random variables are represented as the linear combination of the independent random variables. The second method is based on the mixtures and uses the conditional independency random of variables. In the third one we describe the dependency of random variables using copulas. These methods let us reduce the studied models (the random sum of random variables in our case), to the independent form. So, we can use the classical methods connected with independent case.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 109-122